2004
DOI: 10.1099/jmm.0.45803-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic, non-sporulating, Gram-positive bacilli bacteraemia characterized by 16S rRNA gene sequencing

Abstract: Owing to the difficulties in identifying anaerobic, non-sporulating, Gram-positive bacilli in clinical microbiology laboratories, the epidemiology and clinical spectrum of disease of many of these bacteria have been poorly understood. The application of 16S rRNA gene sequencing in characterizing bacteraemia due to anaerobic, non-sporulating Gram-positive bacilli during a 4-year period is described. The first case of Olsenella uli bacteraemia, in a patient with acute cholangitis, is also reported. Among 165 blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…We detected the species, respectively, in the DGGE profiles of donors 6 and 5. Upon identifying O. uli-associated bacteraemia in a patient with acute cholangitis but no evidence of dental disease, Lau et al (2004b) suggested that the bacterium responsible for the infection was of GI origin. There are currently only two reports of the isolation of G. pamelaeae in the literature: one strain was isolated from the sigmoid region of the colon of a 33-year-old male patient suffering from acute Crohn's disease (Würdemann et al, 2009); the other was isolated in pure culture from an 82-year-old patient with disseminated rectosigmoid carcinoma with fresh blood and mucus in his stool (Woo et al, 2010).…”
Section: Dgge Analysis Of the Faecal 'Atopobium Cluster' Populationmentioning
confidence: 99%
“…We detected the species, respectively, in the DGGE profiles of donors 6 and 5. Upon identifying O. uli-associated bacteraemia in a patient with acute cholangitis but no evidence of dental disease, Lau et al (2004b) suggested that the bacterium responsible for the infection was of GI origin. There are currently only two reports of the isolation of G. pamelaeae in the literature: one strain was isolated from the sigmoid region of the colon of a 33-year-old male patient suffering from acute Crohn's disease (Würdemann et al, 2009); the other was isolated in pure culture from an 82-year-old patient with disseminated rectosigmoid carcinoma with fresh blood and mucus in his stool (Woo et al, 2010).…”
Section: Dgge Analysis Of the Faecal 'Atopobium Cluster' Populationmentioning
confidence: 99%
“…Also a group in Hong Kong also reported that 18% of clinically significant bacteremia caused by anaerobic, gram-positive bacilli were related to E. lenta [2]. Furthermore, E. lenta bacteremia is primarily community acquired [2,3].…”
Section: Case Reportmentioning
confidence: 99%
“…A few studies reported the susceptibilities of E. lenta [3,6,7,15]. In the article by Mosca et al, including 29 strains of E. lenta clinical isolated, all were susceptible to clindamycin, piperacillin and imipenem [15].…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations